Korean Drama Fever—Expanding English Lexicon through Watching English-Subtitled K-Dramas: The Case of Non-Compositional Multiword Expressions - Hsu, Wenhua (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
This research was prompted by the phenomenon of binge-watching Korean television series (K-drama) amongst college students in Taiwan, where English as a foreign language (EFL) is a required course. The researcher-teacher sought to create a pedagogically useful list of the frequent semantically non-compositional multi-word expressions (MWEs) for EFL learners with K-drama fever who often binge-watch K-dramas. A corpus of 25+ million English subtitled words derived from 240 K-dramas across different genres was compiled. Based upon a set of criteria (frequency, range, meaningfulness, well-formedness, non-decomposability and semantic non-compositionality), a total of 326 MWEs of 2 to 6 words were selected. The 326 phrasal expressions are mostly composed of the first 3000 word families. As with other individual word lists, it is hoped that the listing of the non-compositional MWEs may serve as a reference for General English teachers.